Analysis of the dairy farmer in the village of Lubuk Tilan Subdistrict Dayun Siak Regency - Teguh Pramono; Rita Yani Iyan; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to know the amount of the costs, revenues and earnings (profits) received by cattle farmers in the village of Lubuk Tilan Subdistrict Dayun Siak Regency. By using several theory production then variable observed is capital and production cost of Fixed Cost and Variable Cost.The determination of the location of the research is determined by purposive sampling, with consideration at this location many of the people who have jobs or work sideline raising beef cattle originating from the Siak Regency Government help with shifts and gaduhan. This study uses census techniques with the respondent as much as 33 people. Respondents were grouped into two groups, namely the groups I and II in accordance with the number of livestock ownership. A data analysis method used in this research is descriptive qualitative. Data retrieval is done by means of observation, interview and by using a list of questionsThe results showed that the average costs, revenues and earnings (profits) dairy farmer in the village of Lubuk Tilan Subdistrict Dayun Siak Regency in the group I is Rp. 12.577.160 and group II amounted to Rp. 17.164.188. The average revenue earned group I amounting to Rp. 114.800.000 and group II amounted to Rp. 175.125.000 so each group earn income or profit of Rp 102.222.840 and Rp 163.053.357.Keywords: Cattle Farmers, Costs, Income.